ANALYSIS OF COMMUNICATION AND PUNISHMENT ON EMPLOYEE PERFORMANCE WITH WORK DISCIPLINE AS AN INTERVENING VARIABLE AT PT PLN (PERSERO) UP3 PEMATANGSIANTAR - Ahmad Taufik; Mesra B; Muhammad Isa Indrawan; Kiki Farida Ferine (RADJA PUBLIKA, 2025)
This study aims to analyze the effect of communication and punishment on employee performance with work discipline as an intervening variable at PT PLN (Persero) UP3 Pematangsiantar. The research method used is quantitative with the Partial Least Square-Structural Equation Modeling (PLS-SEM) approach. The study population was all 117 permanent employees of PT PLN (Persero) UP3 Pematangsiantar who also served as research samples. The results showed that communication had a positive and significant effect on employee performance and work discipline. Punishment also had a positive and significant effect on employee performance and work discipline. In addition, work discipline was proven to have a positive and significant effect on employee performance. Other findings showed that work discipline played a role as an intervening variable in the relationship between communication and performance, as well as the relationship between punishment and employee performance. The R-square value of work discipline was 0.844 and employee performance was 0.863, which means that this research model has strong explanatory power. The practical implications of this research are the need for company management to clarify superior instructions, socialize punishment rules, especially those related to layoffs, in a transparent manner, improve work discipline development, and provide more training and trust to employees so that they are able to work independently.